LIVING TREES IN PILGRIMAGE - Odiljonov Khojiakbar Zokirjon oglu (Galaxy International Interdisciplinary Research Journal, 2022)
About the fact that the old trees in the shrines of the regions of Uzbekistan are still alive for centuries. Observation and comparison methods were used in writing this article. In several provinces, the age of the living trees in the shrines has been highlighted.